Trust transitivity algorithm based on multiple influencing factors for grid environment - ZHANG Lin1; WANG Ru-chuan1; WANG Hai-yan1 (Tongxin xuebao)
A trust deployment scheme based on layered idea was given for grid environment,which reduced the man-agement costs of system.The fine-grain trust model was proposed which was based on interaction capability and honesty ability.It enhanced the rationality of the model.At the same time,4 influencing factors about trust transitivity were dis-cussed,such as cycle path,path length threshold,node honesty threshold and further trust information.On this condition,the trust transitivity algorithm for grid was studied which was based on depth-first traversal.Example and experimental results show that the model and algorithm are feasible and correct.